2023
DOI: 10.3390/cells12121607
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Faceted Nature of Renalase for Mitochondrial Dysfunction Improvement in Cardiac Disease

Abstract: The cellular mechanisms and signaling network that guide the cardiac disease pathophysiology are inextricably intertwined, which explains the current scarcity of effective therapy and to date remains the greatest challenge in state-of-the-art cardiovascular medicine. Accordingly, a novel concept has emerged in which cardiomyocytes are the centerpiece of therapeutic targeting, with dysregulated mitochondria as a critical point of intervention. Mitochondrial dysfunction pluralism seeks a multi-faceted molecule, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 170 publications
0
4
0
Order By: Relevance
“…RNLS: A truncation (deletion/insertion) variant in the gene for renalase ( RNLS ) on chromosome 10q was first identified in an Arab family with autosomal recessive congenital cataract [ 131 ]. RNLS functions as a secreted flavin adenine dinucleotide (FAD)-dependent monoamine oxidase involved in catecholamine metabolism and may play a role in mitigating mitochondrial dysfunction [ 132 ].…”
Section: Widely Expressed Genes For Inherited and Age-related Cataractmentioning
confidence: 99%
“…RNLS: A truncation (deletion/insertion) variant in the gene for renalase ( RNLS ) on chromosome 10q was first identified in an Arab family with autosomal recessive congenital cataract [ 131 ]. RNLS functions as a secreted flavin adenine dinucleotide (FAD)-dependent monoamine oxidase involved in catecholamine metabolism and may play a role in mitigating mitochondrial dysfunction [ 132 ].…”
Section: Widely Expressed Genes For Inherited and Age-related Cataractmentioning
confidence: 99%
“…This initial stage of apoptosis is potentially reversible by preventing the externalization of membrane PS residues [277,[282][283][284][285] to block inflammatory cells from detecting and removing injured cells that may remain functional [76,[286][287][288][289]. If the second phase of apoptotic cell death is reached, it is usually not reversible and involves the degradation of nuclear deoxyribonucleic acid (DNA) [136,137,167,169,[290][291][292][293][294]. The second stage of apoptosis consists of mitochondrial membrane depolarization, cytochrome c release, and caspase activation [136,193,252,290,[295][296][297][298][299][300].…”
Section: Cellular Mechanisms Of Oxidative Stress Energy Metabolism An...mentioning
confidence: 99%
“…In particular, microglia are important for removing damaged cells during membrane PS externalization and apoptosis [106,131,145,277,278,298,308,[324][325][326][327]]. Yet, microglia can lead to the generation of oxidative stress through the production of ROS [8,165,167,246,250,[328][329][330][331], which can require modulation by non-coding RNAs [251,[332][333][334][335][336], Wnt signaling [27,28,106,115,276,[337][338][339], and trophic factor pathways with erythropoietin (EPO) [27,[340][341][342][343][344][345][346]. In other scenarios, microglial cells can be helpful for protection during amyotrophic lateral sclerosis [347], remove brain amyloid [348,349], and preserve cholesterol homeostasis with autophagy …”
Section: Cellular Mechanisms Of Oxidative Stress Energy Metabolism An...mentioning
confidence: 99%
“…), and genetic factors [17,18]. Cardiomyocytes are extremely vulnerable to oxidative stress and have limited regenerative capacity [19,20]. A large amount of evidence has shown that both GSLs and H 2 S have cardio-protective effects.…”
Section: Introductionmentioning
confidence: 99%